PENGOLAHAN REBUNG SEBAGAI PANGAN FUNGSIONAL SUMBER SERAT. - Supriyatna , Nana (JURNAL BORNEO AKCAYA, 2014)
Research drying processed snack food seasoned with bamboo shoot base has been done with the aim of studying the seasoned dried bamboo shoot processing as a functional food source of fiber. The study involved treatment of soaking in a solution of salt and seasoning giving the dried bamboo shoots. The results of the research provided that the drying treatment using a drying oven gave shape to the drying temperature 40 to 60 Â° C, humidity 60%. The results of the research provided that the drying treatment using a drying oven gave shape to the drying temperature 40 to 60 Â° C, 60% humidity and drying time of 7 hours with the characteristics of dried bamboo shoots water content of 12.2%, 10.9%, and flower power rendemen 11, 9%. Nutrition content spiced dried bamboo shoots are not much different between the formulations in which the crude fiber content between 2.84 to 4.60%, from 11.1 to 15.2% water, 10.5 to 13.02 ash, protein 20.5 to 23 , 4%, water activity from 0.568 to 0.789 and 4.95 to 5.40% fat. This spiced dried bamboo shoots can qualify functional food because it contains nutritional components and coarse fibers that have a specific physiological function, hold harmless and beneficial to health. Panelist organoleptic value and acceptance is highest in dried bamboo shoots seasoned formulation instant seasoning barbeque flavor panelists favored by a score of 3.8